2020
DOI: 10.1038/s41598-020-78865-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of primary breast cancers using dedicated breast PET and whole-body PET

Abstract: Metabolic imaging of the primary breast tumor with 18F-fluorodeoxyglucose ([18F]FDG) PET may assist in predicting treatment response in the neoadjuvant chemotherapy (NAC) setting. Dedicated breast PET (dbPET) is a high-resolution imaging modality with demonstrated ability in highlighting intratumoral heterogeneity and identifying small lesions in the breast volume. In this study, we characterized similarities and differences in the uptake of [18F]FDG in dbPET compared to whole-body PET (wbPET) in a cohort of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The development of new precision radiotracers binds imaging activity to specific clinical targets, advancing personalized (or precision) medicine [1][2][3][4]. In addition to scanning of the body with sequentially performed whole-body (WB) PET/CT (computed tomography) scanners and emerging simultaneous PET/MRI (magnetic resonance imaging), the applications for PET imaging increasingly involve the visualization of specific organs with dedicated systems [5][6][7][8]. Compared to WB PET scanners, an organ-targeted PET system is capable of higher efficiency, higher spatial resolution, and higher signal-to-noise ratio, resulting in better image contrast and enabling more precise PET examinations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of new precision radiotracers binds imaging activity to specific clinical targets, advancing personalized (or precision) medicine [1][2][3][4]. In addition to scanning of the body with sequentially performed whole-body (WB) PET/CT (computed tomography) scanners and emerging simultaneous PET/MRI (magnetic resonance imaging), the applications for PET imaging increasingly involve the visualization of specific organs with dedicated systems [5][6][7][8]. Compared to WB PET scanners, an organ-targeted PET system is capable of higher efficiency, higher spatial resolution, and higher signal-to-noise ratio, resulting in better image contrast and enabling more precise PET examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to WB PET scanners, an organ-targeted PET system is capable of higher efficiency, higher spatial resolution, and higher signal-to-noise ratio, resulting in better image contrast and enabling more precise PET examinations. Indeed, an organ-targeted PET camera with optimized geometry can position detectors in close proximity to the organ of interest to facilitate (1) more efficient gamma-ray detection; (2) higher spatial resolution; and (3) reduced unwanted signal from elsewhere in the body, improving the noise-equivalent count rate (NECR) within the field of view (FOV) due to a reduction of false coincidences [7][8][9][10]. Potentially, this may significantly lower a radiotracer dose, thereby reducing radiation exposure associated with PET molecular imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The observed qualitative differences in spatial and signal intensity heterogeneity in D-PET may be largely driven by the higher voxel resolution and tumor tissue fraction. In a comparative study, spatial heterogeneity features showed statistically significant differences between D-PET and WB-PET [ 6 ]. The precise quantification of tumor heterogeneity may allow an accurate prediction of ALN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Since WB-PET/CT is performed with patients in the supine position, there is a collapse of breast volume and blurring owing to respiratory motion [ 4 , 5 ]. In contrast, Mammi-PET comprises a single ring detector that translates axially over the length of the breast; the prone position enables full-breast volume imaging by avoiding breast compression [ 6 ]. The Lymph-PET device contains movable double-planar confronted detectors with an axilla capability view for precisely detecting hot lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the limited spatial resolution of whole-body PET/CT to detect small breast cancers, high-resolution dedicated breast PET (dbPET) was developed for the detection of early-stage breast cancers. Previous reports have shown that ring-shaped dbPET can visualize smaller breast cancers better than whole-body PET/CT [ 6 , 7 ]. In addition, since dbPET has a highly sensitive detector and does not use X-ray CT to perform attenuation correction, it is expected to greatly reduce the radiation dose to patients when it is used alone compared to whole-body PET/CT for local assessment and screening of breast cancer.…”
Section: Introductionmentioning
confidence: 99%